Chapter 4 A continuum of recordkeeping? The possibilities and challenges of born-digital public records in Denmark and Sweden - Klareld, Ann-Sofie (Taylor & Francis, 2024)
This chapter explores the relationship between public agencies and archival authorities in Denmark and Sweden regarding record keeping practices, born digital records, and archival legislation. We provide a 360-degree look at record keeping within the Nordic Model, taking our point of departure from the records continuum model. The Danish and Swedish approaches we discuss predate the records continuum model yet share commonalities with it in their conceptualization of archives and record keeping. By using the four dimensions of the model - Create, Capture, Organize and Pluralize - the chapter discusses the archiving of born digital records in two highly digitised societies. The case studies of Denmark and Sweden explore their intertwined yet distinct administrative and archival traditions of the two neighbouring countries within the context of the Nordic Model, in addition to considering how they each complement and challenge traditional continuum thinking, noting the ad hoc pragmatism prevalent in the Nordic archives' reactions to the challenges posed by digitisation. By way of conclusion, we urge archival theorists and practitioners in the Nordic countries to rethink the relationship between archives and governmental administrations along the lines laid out in the Records Continuum Model.